2012
DOI: 10.1111/j.1600-0714.2012.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel missense mutation in PAX9 gene associated with familial tooth agenesis

Abstract: PAX9 is a transcription factor deeply involved in the gene networks that regulate odontogenesis. To date, only a restricted number of mutations in this gene have been associated with non-syndromic tooth agenesis. Six families segregating non-syndromic oligodontia/hypodontia were screened for mutations in PAX9 gene. A novel missense mutation lying in the exon 2 close to the end of the paired domain in three families was identified. Heterozygous mutation C503G is expected to result in an alanine-to-glycine amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several genes, such as EDA, MSX1, PAX9, WNT10A, and WNT10B, have been identified as causative for non-syndromic human tooth agenesis [1][2][3][4][5]. Germline pathogenic variants (GPVs) in each of these causative genes lead to tooth deficiencies, and the sites of tooth defects, produced by each gene, are distinctive.…”
Section: Introductionmentioning
confidence: 99%
“…Several genes, such as EDA, MSX1, PAX9, WNT10A, and WNT10B, have been identified as causative for non-syndromic human tooth agenesis [1][2][3][4][5]. Germline pathogenic variants (GPVs) in each of these causative genes lead to tooth deficiencies, and the sites of tooth defects, produced by each gene, are distinctive.…”
Section: Introductionmentioning
confidence: 99%
“…The genotypes of 193 patients with 74 PAX9 variants are shown in Supplementary Table S1 ( Stockton et al, 2000 ; Nieminen et al, 2001 ; Das et al, 2002 ; Frazier-Bowers et al, 2002 ; Boyadjiev et al, 2003 ; Das et al, 2003 ; Lammi et al, 2003 ; Mostowska et al, 2003 ; Jumlongras et al, 2004 ; Klein et al, 2005 ; Zhao et al, 2005 ; Kapadia et al, 2006 ; Mostowska et al, 2006 ; Hansen et al, 2007 ; Tallón-Walton et al, 2007 ; Zhao et al, 2007 ; Guala et al, 2008 ; Wang et al, 2009a ; Wang et al, 2009b ; Haldeman-Englert et al, 2010 ; Pawlowska et al, 2010 ; Bergendal et al, 2011 ; Mendoza-Fandino et al, 2011 ; Paixão-Côrtes et al, 2011 ; Suda et al, 2011 ; Wang et al, 2011 ; Liang et al, 2012 ; Wang et al, 2012 ; Zhu et al, 2012 ; Mostowska et al, 2013a ; Arte et al, 2013 ; Mostowska et al, 2013b ; Boeira and Echeverrigaray, 2013 ; Mitsui et al, 2014 ; Thimmegowda et al, 2015 ; Haddaji Mastouri et al, 2016 ; Liang et al, 2016 ; Shahid et al, 2016 ; Yu et al, 2016 ; Choi et al, 2017 ; Daw et al, 2017 ; Murakami et al, 2017 ; Wong et al, 2018 ; Sun et al, 2021 ). We found that PAX9 -related NSO accounted for 78.2% of the 193 patients, non-syndromic hypodontia for 18.1%, and syndromic oligodontia account for 2.6%.…”
Section: Resultsmentioning
confidence: 99%
“…First genes identified in tooth agenesis were reported to be PAX-9 (paired box 9) and MSX-1 (muscle segment homeobox 1). 32,33 Many different mutations in genes such as MSX-1 and PAX-9 might cause tooth agenesis. It was reported that MSX-1 and PAX-9 play a significant role in mediating direct epithelial-mesenchymal interactions during in the early stages of tooth development especially bud and cap stages.…”
Section: Genetic Factorsmentioning
confidence: 99%